The clinical diagnosis of hemangioma is not always easy - Botrugno, F (European Journal of Pediatric Dermatology, 2012)
An 8-month-old girl was first observed for a lesion of the right hand. Her mother said that the tumor had a dot-like appearance at birth, then grew up to the 5th month reaching its actual size. The physical examination showed in correspondence with the radial surface of the proximal phalanx of the right index an about 6 mm in size, pink nodule with tense-elastic consistency, clearly demarcated on palpation, not warmer than the surrounding tissues. An ultrasonography showed an isoechoic formation completely devoid of vascular signals. Failing to do a clinical diagnosis, we decided to remove the nodule. The histological examination showed a neoformation of endothelial cells with a tendency to the formation of vascular lumens of small size surrounded by thickened connective, leading to the final diagnosis of hemangioma.